Onboarding as a factor of reducing staff turnover in transport and logistics companies: experience of implementing standardized training programs - Kovalchuk, Mykola (Global Prosperity, 2023)
Abstract. This article explores how onboarding can become a real tool for reducing staff turnover in transport and logistics companies. The focus is not only on the theory of onboarding, but also on its practical role in building trust, reducing stress, and supporting new employees from their first days at work. The text highlights why turnover in this sector is particularly high: tough schedules, demanding physical tasks, and the absence of clear guidance often push people to quit early. Against this background, onboarding acts as a bridge between expectations and reality, showing newcomers that they are not left alone with difficulties. The article examines international and local practices of implementing standardized training programs. These programs combine technical learning, safety modules, communication skills, and mentorship, creating a structured and repeatable process that supports every new employee. Evidence shows that such approaches reduce first-year resignations, improve motivation, and strengthen team stability. The conclusions underline that onboarding is not a formal procedure but an investment in people. For transport and logistics companies, where precision and reliability are vital, a well-organized onboarding system is more than a human resources tool - it is a strategic necessity that directly affects competitiveness and long-term growth.